Effect of head-down tilt on clinical outcome and cerebral perfusion in ischemic stroke patients: A case series - Zhao, Zi-Ai; Zhang, Nan-Nan; Tao, Lin; Cui, Yu; Li, Meng; Qi, Shou-Liang; Chen, Hui-Sheng (Frontiers in Neurology, 2022)
Background The effect of head position on stroke is not clear. The current study aimed to observe the effect of head-down tilt on acute ischemic stroke (AIS) patients with large vessel occlusion. Methods We observed the influence of head-down tilt position on clinical outcomes, myocardial enzymogram and N-terminal pro b-type Natriuretic Peptide in 4 AIS patients who suffered early neurological deterioration (END). Cerebral perfusion imaging was performed in 3 patients using arterial spin labeling. Results In series of AIS patients with END, head down tilt (-20°) prevented further neurological deterioration and improved clinical outcomes. An increase in cerebral blood flow was observed by arterial spin labeling after head down tilt treatment. No obvious adverse events occurred. Conclusion The case series suggest that head-down tilt may improve clinical outcome in AIS patients through increasing the cerebral perfusion with no obvious adverse events. The finding needs to be confirmed in future clinical trials.